Irisin directly stimulates osteoclastogenesis and bone resorption in vitro and in vivo - Estell, Eben G (eLife, 2020)
Irisin, a skeletal-muscle secreted myokine, facilitates muscle-bone crosstalk and skeletal remodeling in part by its action on osteoblasts and osteocytes. In this study, we investigated whether irisin directly regulates osteoclasts. In vitro, irisin (2–10 ng/mL) increased osteoclast differentiation in C57BL/6J mouse bone marrow progenitors; however, this increase was blocked by a neutralizing antibody to integrin α(V)β(5). Irisin also increased bone resorption on several substrates in situ. RNAseq revealed differential gene expression induced by irisin including upregulation of markers for osteoclast differentiation and resorption, as well as osteoblast-stimulating ‘clastokines’. Forced expression of the irisin precursor Fndc5 in transgenic C57BL/6J mice resulted in lower bone mass at three ages and greater in vitro osteoclastogenesis from Fndc5-transgenic bone marrow progenitors. This study demonstrates that irisin acts directly on osteoclast progenitors to increase differentiation and promote bone resorption, supporting the tenet that irisin not only stimulates bone remodeling but may also be an important counter-regulatory hormone.